The Transformation of Authoring Tools in Content Development: From Articulate Storyline to Artificial Intelligence (AI) Integration - Heni Yulianti; Handini Handini; Alpina Pebrianti; Gunawan Gunawan; Nina Nisrina (Indonesian Journal of Applied Science and Technology, 2023)
The rapid development of digital technology has significantly transformed the development of learning media, particularly through the evolution of authoring tools from multimedia-based platforms such as Articulate Storyline toward the integration of artificial intelligence (AI). This study aims to analyze the paradigm shift in the development of digital learning media and examine its implications for instructional design and learning effectiveness. The study employed a literature review method by analyzing 15 relevant scientific journal articles related to authoring tools, Articulate Storyline, and the application of AI in learning. The findings indicate that the development of authoring tools not only enhances the interactivity of learning media but also enables the integration of AI technology that supports personalized learning, automated content creation, and real-time analysis of students’ learning performance. However, the implementation of these technologies also requires improved digital competencies among educators and careful consideration of ethical issues related to data usage. Therefore, the transformation of authoring tools reflects a shift in digital learning strategies toward systems that are more adaptive, interactive, and learner-centered.